Studies on Indian Mites. 4. Three new Pachylaelaps with a key to the species (Acarina: Mesostigmata). - Bhattacharyya, S. K. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Three new species of the genus Pachylaelaps Berlese are described from India: P. femoralis, P. dorsalis and P. setosus. Nomenclatural Acts dorsalis Bhattacharyya, 1970 (Pachylaelaps), spec. n. femoralis Bhattacharyya, 1970 (Pachylaelaps), spec. n. setosus Bhattacharyya, 1970 (Pachylaelaps), spec. n.